Technical Aspects of in vivo Small Animal CMR Imaging - Li, Hao; Abaei, Alireza; Metze, Patrick; Just, Steffen; Lu, Qinghua; Rasche, Volker (Frontiers in Physics, 2020)
Cardiovascular magnetic resonance (CMR) imaging has become an accurate and versatile imaging modality to visualize the cardiovascular system in normal or abnormal conditions. In preclinical research, small rodent animal models of human cardiovascular diseases are frequently used to investigate the basic underlying mechanism of normal and abnormal cardiac function and for monitoring the disease progression under therapy. Technical improvements have enabled the transfer of CMR to small animal research, and as such made this non-invasive technique available to provide insights into cardiac morphology, function, perfusion, and pathophysiology in small animal cardiac disease models. This article reviews the basic technical approaches to in vivo small animal magnetic resonance imaging and its variants for the most promising applications.